Coordinated social communication in toddlers with and without autism spectrum disorder during a home observation. (September 2022) - Delehanty, Abigail; Wetherby, Amy M.
Background & Aims: Social communication and language skills have been found to be important predictors of long-term outcomes in individuals with autism spectrum disorder (ASD). However, the development of coordinated social communication (i.e., gestures and sounds or words) remains relatively understudied in young children with ASD and developmental delays (DD). This study used a prospective, longitudinal design and granular observational coding to document the coordination of gestures, sounds, and words in a large, heterogeneous sample of toddlers identified with ASD, DD, or typical development (TD) during a naturalistic home observation. Specific aims were: (1) to compare rates per minute and proportions of coordinated child communicative acts across groups; (2) to examine concurrent relationships between coordinated communication and measures of social communication and autism symptoms; and (3) to examine prospective relationships between coordinated communication, receptive and expressive language skills, and autism symptoms collected at 3 years of age. Methods: At a mean age of 20.3 months (SD = 2.0), 211 children (nASD  = 121; nDD  = 46; nTD  = 44) participated in everyday activities with a parent during an hourlong home observation. Rates per minute and proportions of gestures, sounds and words, as well as temporally overlapping gesture + sound, gesture + word, and gesture + phrase combinations, were compared using one-way ANOVA. Pearson product moment correlations between coordinated communicative acts and measures of social communication, language, and autism symptoms were examined. Results: On average, children with ASD used sounds and gesture + sounds at significantly lower rates than DD and TD groups, who did not differ. Children with ASD and DD coordinated gesture + single words and gesture + phrases at significantly lower rates than the TD group. Groups did not differ with respect to the rate per minute at which they used gestures alone. Children with TD used a smaller proportion of sounds alone and higher proportions of words and phrases, with and without coordinated gestures, than ASD and DD groups. Children with ASD and DD used a significantly higher proportion of gestures alone than children with TD. Rates per minute and proportions of single words and gesture + words had significant correlations with measures of social communication, language skills, and autism symptoms. Conclusions: Results suggest that a significantly lower rate per minute of sounds and gesture + sound combinations was a distinguishing feature of ASD in our sample. Further, limited use of single words and gesture + single words was observed in children ASD and DD. Significant prospective relationships between single words and gesture + words with language skills measured over a year later underscores the importance of acquiring these forms. Implications: Results support the idea that clinicians should include opportunities to observe and encourage coordinated social communication while screening and assessing young children for DD and ASD in the home environment. The significant associations between rate of single words and gesture + word combinations with language development over a year later have implications for incorporating intervention targets that encourage the use of gesture-speech combinations.